BARRIERS AFFECTING EFFECTIVE MONITORING AND EVALUATION OF POVERTY ALLEVIATION PROJECTS WITHIN WATERBERG DISTRICT - Dipela, Mmaphuti Percy; Mohapi, Boitumelo Joyce (Social Work/Maatskaplike Werk, 2021)
Community projects aimed at alleviating poverty under the supervision of social workers employed by the Department of Social Development (DSD) in the Waterberg district of the Limpopo Province seem to be collapsing. This prompted the researchers to undertake a qualitative study using a contextual, descriptive and explorative research design aimed at obtaining an in-depth understanding of the monitoring and evaluation (M&E) mechanisms applied in supporting community projects for alleviating poverty. This article reports on findings based on interviews conducted with 21 participants. The study identified a lack of knowledge and training, as well as poor management and supervisor support as contributors towards weak M&E.